Cover Feature: Bell–like [Ga5] clusters in Sr3Li5Ga5: synthesis, crystal structure and bonding analysis. (Z. Anorg. Allg. Chem. 18/2021). Issue 18 (21st September 2021) - Kotsch, Matthias; Prots, Yurii; Ormeci, Alim; Senyshyn, Anatoliy; Kohout, Miroslav; Grin, Yuri
Abstract : This cover picture shows the unique bell‐like [Ga5 ] cluster and its corresponding ELI‐D maxima, in front of a drawing of an old school bell. First observed in the related compound Eu3 Li5 Ga5 these clusters are the first and only known galliumclusters to be nonconvex, which makes an investigation of the intra cluster bonding of particular interest. Initially hindered by the presence of europium, an application of the electron localizability approach (ELI‐D) became possible with Sr3 Li5 Ga5 due to the absence of f electrons. The resulting insights into the bonding situation are described in great detail in our article 202100147 .